The murid herpesvirus-4 gH/gL binds to glycosaminoglycans. - Laurent Gillet; Susanna Colaco; Philip G Stevenson (PLoS ONE)
The first contact a virus makes with cells is an important determinant of its tropism. Murid Herpesvirus-4 (MuHV-4) is highly dependent on glycosaminoglycans (GAGs) for cell binding. Its first contact is therefore likely to involve a GAG-binding virion glycoprotein. We have previously identified two such proteins, gp70 and gp150. Gp70 binds strongly to GAGs. However, deleting it makes little difference to MuHV-4 cell binding or GAG-dependence. Deleting gp150, by contrast, frees MuHV-4 from GAG dependence. This implies that GAGs normally displace gp150 to allow GAG-independent cell binding. But the gp150 GAG interaction is weak, and so would seem unlikely to make an effective first contact. Since neither gp70 nor gp150 matches the expected profile of a first contact glycoprotein, our understanding of MuHV-4 GAG interactions must be incomplete. Here we relate the seemingly disconnected gp70 and gp150 GAG interactions by showing that the MuHV-4 gH/gL also binds to GAGs. gH/gL-blocking and gp70-blocking antibodies individually had little effect on cell binding, but together were strongly inhibitory. Thus, there was redundancy in GAG binding between gp70 and gH/gL. Gp150-deficient MuHV-4 largely resisted blocks to gp70 and gH/gL binding, consistent with its GAG independence. The failure of wild-type MuHV-4 to do the same argues that gp150 is normally engaged only down-stream of gp70 or gH/gL. MuHV-4 GAG dependence is consequently two-fold: gp70 or gH/gL binding provides virions with a vital first foothold, and gp150 is then engaged to reveal GAG-independent binding.